EXPLORING SOIL SALINITY ASSESSMENT METHODS: INSIGHTS, INNOVATIONS, AND THE PROMISE OF REMOTE SENSING FOR SUSTAINABLE AGRICULTURE AND ENVIRONMENTAL CONSERVATION (Scientific journal of the Fergana State University, 2024)
The assessment of soil salinity is crucial for maintaining agricultural sustainability and effective environmental management. In this review paper, we evaluate various soil salinity assessment methods, including field-based techniques, laboratory analysis methods, and remote sensing technologies, considering their strengths, limitations, and implications. Among these methods, remote sensing emerges as a promising approach due to its cost-effectiveness, scalability, and potential for future advancements. Remote sensing technologies, such as satellite imagery and aerial surveys, offer distinct advantages in soil salinity assessment, providing a non-invasive means of monitoring large geographic areas and enabling timely detection and mapping of soil salinity patterns. Moreover, remote sensing allows for the integration of multispectral and hyperspectral data, enhancing the accuracy of assessment results. The accessibility of remote sensing data and the development of intelligent algorithms further contribute to its applicability across diverse environmental contexts. This review highlights the importance of soil salinity assessment and emphasizes the potential of remote sensing technologies to inform evidence-based management strategies for mitigating the adverse effects of soil salinity on agricultural productivity and environmental sustainability.